Comparative Analysis of Energy Efficiency in High-Voltage Ozone Generators: Resonant Versus Non-Resonant Systems - Tongpian Prombud; Ekkapol Anusurain; Chainarong Wisassakwichai; Choosak Kamonkhantithorn (Energies)
The effective generation of ozone by high-voltage systems is essential for several industrial and environmental purposes. This paper performs a thorough comparative examination of energy efficiency in ozone generators, emphasizing resonant and non-resonant systems. Resonant ozone generators, which utilize tuned electrical circuits for optimal efficiency, are assessed in comparison to non-resonant systems that function without frequency tuning. The comparison analysis includes measures like energy use, ozone generation, and overall system efficiency. Experimental results demonstrate considerable differences in energy consumption between the two generator types, with resonant systems exhibiting substantially more efficiency in the conversion of electrical power into ozone. The resonant systems, producing 120 g/kWh, demonstrate 50% greater efficiency than the non-resonant systems, which generate 80 g/kWh, in terms of ozone production per unit of energy. This study clarifies the operational features, benefits, and drawbacks of each system, offering essential insights for the advancement of ozone-generating technologies in diverse applications.